Multimedia package: Learning how to program in C, plus interactive tutorial / Norsuhana Azman - Norsuhana, Azman (2003)
Multimedia has grown into a technology which is frequently adopted in most of computer-based educational titles lately. Not onl it is implemented in education but it can be seen in business, entertainment and administrative environments. Multimedia has added dimension to the way humans exchange ideas and communicate with machines through a multisensory system. It has provided us with tools and techniques that make communication and comprehension more effective. Due to the fact that multimedia plays a vital part in the way people communicates with machines and its environment, this project has taken the initiative of applying the multimedia concept in its learning package. More over, programming languages such as C is considered an important programmers basic knowledge before moving on to other programming concepts, that makes it suitable to be conveyed as multimedia based learning tool. In ensuring a quality software produced, stages of iterative development process has been adopted by implementing the Rapid Application Development methodology (RAD). RAD opts for iterative development process that will help to detect early faults which in turn helps to shorten the development process. The project focuses on issues such as research methods, reviews made on existing software and surveys on authoring tools. An extensive literature review on subjects that assist in providing information in this project is discussed. Then, moving on to the system design, system implementation, the writing of programs, the testing stage and ending with the delivery process.